5G Network as a Technology to Fight Covid-19 Pan-demic in Indonesia: a Review - U. Mustakim, Hamzah; Montolalu, Billy; Hafidz, Isa (Journal of Computer, Electronic, and Telecommunication (COMPLETE), 2021)
Since March 2020 until now the Covid-19 pandemic has caused a very signifi-cant impact on people's lives in Indonesia. Based on August 2021 data, the num-ber of positive COVID-19 cases reached nearly 4 million cases and the number of recovered patients reached 3.2 million. the use of communication technology is an important part of efforts to overcome the pandemic and help people to access digital health services. Along with this pandemic, Indonesia has just launched 5G network technology with much better performance than 4G technology so that it can be used to create a better healthcare system for patients. This paper provides a review and opportunity for the use of 5G technology for the development of a digital health service system.